Consistency of technical and performance based rowing variables in single sculling - Draper, C.; Smith, R. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Possibilities in competitive rowing exist for further performance enhancements in a well prepared race design and a more individualised training program. The purpose of this study was to examine the consistency of key biomechanical variables and to describe their effect on boat motion. Elite single scullers (n=12) rowed at five stroke rates in an instrumented single scull. The results revealed a high consistency of the technical rowing variables in sculling. In particular, the applied bow and stroke pin and footstretcher forces and angles differed across individuals and were not entirely symmetrical producing a net applied boat moment. The investigation revealed that the interaction and relationships between selected variables were more important than any single variable.